An epidemiological survey of bovine Babesia and Theileria parasites in cattle, buffaloes, and sheep in Egypt. Issue 1 (February 2015) - Elsify, Ahmed; Sivakumar, Thillaiampalam; Nayel, Mohammed; Salama, Akram; Elkhtam, Ahmed; Rizk, Mohamed; Mosaab, Omar; Sultan, Khaled; Elsayed, Shimaa; Igarashi, Ikuo; Yokoyama, Naoaki
Abstract Cattle, buffaloes, and sheep are the main sources of meat and milk in Egypt, but their productivity is thought to be greatly reduced by hemoprotozoan parasitic diseases. In this study, we analyzed the infection rates of Babesia bovis, Babesia bigemina, Theileria annulata, and Theileria orientalis, using parasite-specific PCR assays in blood–DNA samples sourced from cattle (n = 439), buffaloes (n = 50), and sheep (n = 105) reared in Menoufia, Behera, Giza, and Sohag provinces of Egypt. In cattle, the positive rates of B. bovis, B. bigemina, T. annulata, and T. orientalis were 3.18%, 7.97%, 9.56%, and 0.68%, respectively. On the other hand, B. bovis and T. orientalis were the only parasites detected in buffaloes and each of these parasites was only found in two individual DNA samples (both 2%), while one (0.95%) and two (1.90%) of the sheep samples were positive for B. bovis and B. bigemina, respectively. Sequence analysis showed that the B. bovis Rhoptry Associated Protein-1 and the B. bigemina Apical Membrane Antigen-1 genes were highly conserved among the samples, with 99.3–100% and 95.3–100% sequence identity values, respectively. In contrast, the Egyptian T. annulata merozoite surface antigen-1 gene sequences were relatively diverse (87.8–100% identity values), dispersing themselves across several clades in the phylogenetic tree containing sequences from other countries. Additionally, the T. orientalis Major Piroplasm Surface Protein (MPSP) gene sequences were classified as types 1 and 2. This is the first report of T. orientalis in Egypt, and of type 2 MPSP in buffaloes. Detection of MPSP type 2, which is considered a relatively virulent genotype, suggests that T. orientalis infection may have veterinary and economic significance in Egypt. In conclusion, the present study, which analyzed multiple species of Babesia and Theileria parasites in different livestock animals, may shed an additional light on the epidemiology of hemoprotozoan parasites in Egypt.